Sosialisasi Penerapan Pajak Penghasilan Final Untuk Usaha Mikro Kecil Menengah - Muti’ah Muti’ah; Ratna Mappanyukki (LPMP Imperium, 2019)
This Community Service Program (PKM) aims to improve knowledge and skills in making simple bookkeeping and calculation of profit/loss as a basis for calculating taxes on Micro, Small and Medium Enterprises (MSMEs) in Meruya Jakarta. This activity has a very mutual relationship with the MSME's communities. The method used in this activity is the scheduled training method. The results of training conducted to MSME actors have implications: (1). It is recommended that every MSME performer keep his or her bookkeeping business properly and correctly as a basis for calculating taxes; (2). Local governments, through the Office of Cooperatives and MSME (Dinas Koperasi dan UMKM), can contribute to providing guidance and training for MSMEs actors, because the results of the business they get contribute to the Regional Budget. Keywords: MSMEs, income tax